The Potential Contribution of Geography Curriculum to Scientific Literacy. Issue 5 (3rd September 2019) - Xuan, Xiaowei; Jin, Qingna; Jo, Injeong; Duan, Yushan; Kim, Mijung
Abstract: Few studies, if any, have systematically investigated the connection or relationship between geography curriculum and scientific literacy. With this realization, in this article, we examined the potential contribution of geography curriculum to developing students' scientific literacy, with China's middle-school geography curriculum as an example. Through content analysis and semi-structured interviews, we found that geography curriculum holds significant potential to develop scientific literacy, especially regarding interpreting data in various formats, scientific reasoning, and interrelationships among science, technology, society, and environment. This study could provide insights for educators to design interdisciplinary programs to develop students' scientific literacy.